Evolution of comovement between commodity futures: does biofuels matter? - Dinçer DEDEOĞLU (Theoretical and Applied Economics, 2014)

(untitled)
In this study, the linkages of commodity futures are investigated for the period 1988:M1-2012:M4. Monthly futures prices for nine commodities are utilized throughout the empirical analyses. As the empirical approach, wavelet analysis is chosen to investigate the comovement of commodity futures. By using wavelet based measure of correlation, the correlation between commodity futures are determined both in time and frequency domain. The results indicate that correlations are low for short, medium and long-run. I also find evidence of a tendency towards an increase in correlations after 2008. This can be the result of the global crisis that has an effect on feedstock costs and energy input prices by putting front a channel through biofuels that links energy and agricultural commodities by increasing the correlation between these commodities after 2008.